Effectiveness of an acellular synthetic matrix in the treatment of hard‐to‐heal leg ulcers. Issue 2 (9th July 2013) - Harding, Keith; Aldons, Pat; Edwards, Helen; Stacey, Michael; Finlayson, Kathleen; Gibb, Michelle; Jenkins, Liz; Shooter, Gary; Lonkhuyzen, Derek Van; Lynam, Emily; Heinrichs, Eva‐Lisa; Upton, Zee
Abstract Hard‐to‐heal leg ulcers are a major cause of morbidity in the elderly population. Despite improvements in wound care, some wounds will not heal and they present a significant challenge for patients and health care providers. A multi‐centre cohort study was conducted to evaluate the effectiveness and safety of a synthetic, extracellular matrix protein as an adjunct to standard care in the treatment of hard‐to‐heal venous or mixed leg ulcers. Primary effectiveness criteria were (i) reduction in wound size evaluated by percentage change in wound area and (ii) healing assessed by number of patients healed by end of the 12 week study. Pain reduction was assessed as a secondary effectiveness criteria using VAS. A total of 45 patients completed the study and no difference was observed between cohorts for treatment frequency. Healing was achieved in 35·6% and wound size decreased in 93·3% of patients. Median wound area percentage reduction was 70·8%. Over 50% of patients reported pain on first visit and 87·0% of these reported no pain at the end of the study. Median time to first reporting of no pain was 14 days after treatment initiation. The authors consider the extracellular synthetic matrix protein an effective and safe adjunct to standard care in the treatment of hard‐to‐heal leg ulcers.